2016
DOI: 10.1515/revneuro-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Role of iso-receptors in receptor-receptor interactions with a focus on dopamine iso-receptor complexes

Abstract: AbstractIntercellular and intracellular communication processes consist of signals and recognition/decoding apparatuses of these signals. In humans, the G protein-coupled receptor (GPCR) family represents the largest family of cell surface receptors. More than 30 years ago, it has been proposed that GPCR could form dimers or higher-order oligomers (receptor mosaics [RMs] at the plasma membrane level and receptor-receptor interactions [RRIs] have been proposed as a new integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 182 publications
(261 reference statements)
0
11
0
Order By: Relevance
“…Atomic force microscopy studies of rhodopsin have also revealed an oligomeric arrangement . There is also a wealth of biochemical evidence of cooperativity in the actions of orthosteric ligands of both class A and class B GPCRs suggesting that many GPCRs participate in oligomerization as part of their functional cycle, perhaps as a means of trafficking, compartmentalization or, for those receptors that are not obligate dimers, a means of dynamically regulating their selectivity or signaling efficiency …”
Section: Oligomeric Versus Monomeric Organization Of Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic force microscopy studies of rhodopsin have also revealed an oligomeric arrangement . There is also a wealth of biochemical evidence of cooperativity in the actions of orthosteric ligands of both class A and class B GPCRs suggesting that many GPCRs participate in oligomerization as part of their functional cycle, perhaps as a means of trafficking, compartmentalization or, for those receptors that are not obligate dimers, a means of dynamically regulating their selectivity or signaling efficiency …”
Section: Oligomeric Versus Monomeric Organization Of Receptorsmentioning
confidence: 99%
“…Interestingly, mutagenesis studies have also identified putative intracellular allosteric sites for synthetic modulators of some chemokine receptors, and novel lipidated peptides (“pepducins”) have been designed to specifically modulate the intracellular surfaces of different GPCRs . Finally, it is worth highlighting that there remain numerous pharmacological examples of GPCRs that display cooperativity in their modes of interaction with both cognate and synthetic ligands, suggesting that the potential for interactions across GPCR oligomeric arrays is also possible …”
Section: Allosteric Modulatory Sites and Their Pharmacologymentioning
confidence: 99%
“…185 Finally, it is worth highlighting that there remain numerous pharmacological examples of GPCRs that display cooperativity in their modes of interaction with both cognate and synthetic ligands, suggesting that the potential for interactions across GPCR oligomeric arrays is also possible. 65,66…”
Section: Allosteric Sites On Gpcrsmentioning
confidence: 99%
“…According to our proposal, cell sentience is based not only on the ion entry into the cell cytoplasm across the plasma membrane ion channels, as suggested by Cook and coauthors, but also on the spontaneous activity of receptors especially of RMs (Fuxe and Agnati, 1985;Agnati et al, 1983Agnati et al, , 2016. These phenomena can likely have peculiar importance for the complex functions of multifunctional sensory nano-antenna carried out by the primary cilia (Handel et al, 1999;Brailov et al, 2000;Green et al, 2012).…”
Section: The Multi Facet Aspects Of Cell Sentiencementioning
confidence: 74%